Perception, Attitude, and Treatment Behaviour of The Community Towards Mental Disorders in Banyumas Raya - Paramita, Hilma; Supriyanto, Irwan; Isnaya, Purwa Riana; Basiran; Lestari, Diyah Woro Dwi; Septianawati, Paramita; Purnama, Meta Mukhsinin (Jurnal Psikiatri Surabaya, 2024)
Introduction: The stigma associated with mental disorders continues to have negative value in Indonesian society, which can influence treatment decisions. This project is aimed at evaluating the public’s perceptions, attitudes, and behavior toward treatment of mental disorders in Banyumas Raya. Methods: This was a quantitative cross-sectional study with 410 respondents who had completed questionnaires on mental health perceptions (Mental Health Knowledge Schedule, MAKS), attitude assessment (the Community Attitudes toward Mental Illness, CAMI), and behavior of choosing traditional treatment or medical treatment in October–November 2022. A descriptive analysis was used, and the relationship was assessed using the chi-square test. Result: Descriptive analysis reveals that 273 (66.6%) respondents live in Banyumas, 167 (40.7%) are senior high school graduates, and 175 (42.7%) have an income of Rp. 1,000,000-Rp. 3,000,000. Bivariate analysis revealed a significant relationship between knowledge and behavior (p<0.05; CI. OR: 0.251). Conclusion: Respondents with a high level of knowledge are more likely to engage in medical behavior.